Effects on the Functionality and Structure of Rice-Pea Composite Protein by Industry-scale Microfluidizer Combined with pH Cycling Treatment - Yunfeng LU; Taotao DAI; Zhaoying LI; Jialong HAN; Ti LI; Chengmei LIU; Jun CHEN (Shipin gongye ke-ji, 2025)
To investigate the solubilization of composite plant protein after co-processing with an industry-scale microfluidizer and pH cycling and to clarify its solubilization mechanism, this paper used rice protein and pea protein as raw materials, a mixed protein solution with a protein ratio of 1:1 and a total protein concentration of 4% were configured. The pH of the mixture was then adjusted to 12 and the solution processed at different pressures in a high-pressure jet mill. The composite protein was then obtained by adjusting the pH of the solution back to neutral. And to characterize the changes in physicochemical properties and structure of composite protein during this process using nitrogen solubility index, particle size, fluorescence spectroscopy, circular dichroism, molecular weight, and other means. Results showed that the nitrogen solubility index of 4% composite protein underwent industry-scale microfluidizer and pH cycling treatment was increased with the increase of pressure, reaching the maximum of 92.67%±0.77% at 120 MPa. The results of scanning electron microscopy and particle size showed that the composite proteins decreased in size and the specific surface area increased after the treatment of the industry-scale microfluidizer. The results of intrinsic fluorescence spectroscopy, surface hydrophobicity, sulfhydryl disulfide bonding, and circular dichroism indicated that the two proteins interacted to form new co-assembly composites. Surface hydrophobicity increased significantly from 4025.33 to 7359.45 (P<0.05), the hydrophobic region increased. Free sulfhydryl content increased significantly from 26.46±0.32 μmol/g to a maximum of 32.66±0.35 μmol/g (P<0.05), while disulphide bonding content decreased significantly from 9.86±0.42 μmol/g to 5.48±0.27 μmol/g (P<0.05). The actual content of α-helices (25.3%) was higher than the theoretical value (21.83%), indicating a transition to a more hydrophilic α-helix in the secondary structure as the treatment pressure increased. Furthermore, the amino acid analysis revealed that the composite protein had a balanced and complete composition of amino acids. Additionally, the emulsification and foaming properties of the treated composite proteins were superior to those of rice and pea proteins due to their high solubility. This study demonstrated that the combination of industry-scale microfluidizer and pH cycling could effectively enhance the functional properties of the composite protein. The findings provide theoretical support for solubilization and modification of plant proteins on an industrial scale.